Second Phase Platelet Aggregation Induced by Adenosine Diphosphate in Patients with Cerebral Vascular Disease and in Control Subjects - Danta, G (Thrombosis and Haemostasis, 1970)
Adenosine diphosphate-induced second phase platelet aggregation was studied in 70 patients with established cerebral vascular disease, 27 patients with chronic cerebral vascular disease taking dipyridamole, and 53 control subjects. The appearances of aggregation graphs relating changes in optical density in platelet-rich plasma to time after addition of adenosine diphosphate are described. An intermediate rate change in optical density was observed between first and second phase aggregation.Induction of second phase aggregation depends on the concentration of adenosine diphosphate and the platelet count of the plasma. Individual rseponses vary greatly, and there is appreciable variability in repeated estimations, but in the same plasma responses to adenosine diphosphate are accurately reproducible.In both patients and controls the mean logarithm of the adenosine diphosphate concentration that just induces second phase aggregation is inversely proportional to the mean platelet count of platelet-rich plasma. At all platelet concentrations studied, the smallest concentration of adenosine diphosphate that brought about second phase aggregation was significantly less in the patients than in controls. There was no significant correlation between the means of the two variables in patients taking dipyridamole. The findings in this group of patients accord with the assumption that dipyridamole favourably affects the abnormal reaction of platelets to adenosine diphosphate in some of the patients with cerebral vascular disease.